Archaeological research at Caution Bay, Papua New Guinea : cultural, linguistic and environmental setting - Richards, Thomas,; David, Bruno, 1962-; Aplin, Ken,; McNiven, Ian J., (Caution Bay studies in archaeology ;, 2016)
In 2008 intensive archaeological surveys began at Caution Bay, located 20km to the northwest of Port Moresby, Papua New Guinea. This was followed by the excavation of 122 stratified sites in 2009-2010, and detailed analysis of the well preserved and abundant faunal, ceramic and lithic finds has continued ever since. The Caution Bay Archaeology Project is providing new and exciting contributions to western Pacific prehistory. It has radically expanded the known geographic distribution of the Lapita Cultural Complex to include, for the first time, the southern coast of Papua New Guinea; it has established the relationship of Lapita to later cultural expressions in this area; it has pinpointed the time of arrival of domesticated animals along the southern coast of Papua New Guinea and, by inference, on the larger island of New Guinea.